"When you're desperate you'll ask anybody": young people's social sources of tobacco - Louise Marsh; Anna Dawson; Rob McGee (Elsevier, 2013)
Abstract Objectives : This study sought to examine young New Zealand smokers' access to social supplies of cigarettes. Methods : A qualitative investigation using 10 focus groups with 66 current young smokers, aged between 15 and 17 years, was conducted throughout New Zealand, between October and December 2011. Transcripts from the focus groups were analysed using NVivo to code the data, from which common themes and critical issues were identified. Results : Family was one of the main sources of tobacco for the young smokers in this study and parents were the leading source, often purchasing tobacco for their children to smoke. Sharing tobacco within groups of friends was also very common. Additional methods were used when young smokers were desperate, including stealing, 'butt scabbing' and asking strangers. Conclusions : Both family and social networks continue to support smoking and supply tobacco to young people. While these networks operate, young people will continue to smoke, despite increased regulations on commercial sales to minors. Implications : Restrictions on commercial sales of tobacco to minors are increasing; however, many young people use multiple sources of tobacco, including social sources. It is likely that young people will increasingly use these social sources in the future. Interventions other than purchase restrictions are important for reducing minors' access to tobacco.